ANALISIS KONVERSI LAHAN PERTANIAN DI KEBUPATEN TANGERANG - Santun R P Sitorus; Riezkiana Putri; Dyah R Panuju (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Land conversion is a term that describes phenomenon of changing land-use from one to other uses permanently. Factors closely associated with land conversion were population growth, economic, and infrastructure development. This study aims are: (1) to determine rate and pattern of farmland conversion in Tangerang District, (2) to know growth rate of population density, economic growth, and development of Tangerang District, and (3) to determine factors affecting conversion of agricultural land in Tangerang District. Land conversion in Tangerang District caused areas of agricultural land decreased 2.4% per year. The agricultural lands were converted into built land. Population density grew unevenly in Tangerang District. The highest population density growth rate occurred ( during 1997-2007 ) in Pasar Kemis (19% ) and Kronjo faced the lowest rate (0.2%). The economic growth rate in the Tangerang District can be seen from the 1997-2007 Gross Regional Domestic Product (GRDP) Tangerang District. In general, service sector has the highest growth rate (3.9%) followed by industrial sector (0.9%) and agriculture sector (0.6%). Meanwhile, mining sector decreased by 4.1% per year. Level of development in Tangerang District analyzed with scalogram shows that in 2003 most of the villages (60.98%) were on 3rd hierarchy, while the rest on 2nd hierarchy (30.18%) and 1st hierarchy (8.84%). In the year 2006, there were an increase in number of villages on 2nd hierarchy and a decrease in number of villages on 3rd hierarchy, while the number of villages on 1st hierarchy were the same. Factors with highly significant (p-level <0.05) influencing agricultural land conversion were GRDP growth of services sector, GRDP of agricultural sector, GRDP of manufacturing industry, educational facilities, economic facilities, accessibility to health facilities, and accessibility to government centre, whereas accessibility to educational facilities was the significant factor (p-level <0.1).